Unveiling the Legacy of Bronze Age Arrow Weapons in Southeast Asia: Function, Technology, and Cultural Significance - González, Leek Lombard; Fontijn, Earle (Insan Akademika Publications, 2023)
This research delves into the intricate past of Bronze Age arrow weapons in Southeast Asia, offering a multifaceted examination of their function and technology. Through archaeological fieldwork, material analysis, comparative studies, and ethnographic research, we illuminate the advanced metallurgical knowledge that allowed the precise blending of copper and tin to create durable bronze alloys. These findings underscore the technological expertise of Bronze Age societies, providing valuable insights into the historical development of metallurgy. Moreover, this study unveils the multifunctional nature of arrow weapons, which played pivotal roles in hunting, warfare, and ceremonial practices, exemplifying the adaptability of Bronze Age communities. The intricate designs and decorations on arrowheads reveal the cultural and spiritual significance of these artifacts, emphasizing their role in belief systems and rituals. Additionally, our research suggests cross-cultural interactions and influences, positioning Southeast Asia as a vital crossroads for ancient trade networks and cultural exchange. This interdisciplinary approach brings together archaeology, materials science, and ethnography, highlighting the potential of collaborative research in unraveling the complexities of ancient societies. Ultimately, this study not only contributes to our understanding of arrow weapons but also underscores their broader implications for the fields of archaeology, anthropology, and the study of material culture. It reaffirms the enduring value of historical research and the significance of preserving and comprehending the material heritage of diverse regions, illuminating the rich tapestry of human history.